Relevant membrane anatomy and operative strategy for laparoscopic radical resection of middle transverse colon cancer - Li Zhixiong; Xu Yanchang; Wang Xiaojie; Wu Haiyan; Li Junpeng; Ren Jie (结直肠肛门外科)
Although the incidence of transverse colon cancer is relatively low, its location in the mid-hindgut, with fusion to the anterior mesentery and posterior peritoneum. Therefore, the surgical procedureof transverse colon cancer, particularly for middle transverse colon cancer, is more complicated. Scholars have focused on how to correctly understand the membrane anatomy of the transverse colon and its mesentery, standardize surgical procedures, transform complex radical resection of middle transverse colon cancer into a comprehensible and easily executable operation. Currently, few literatures provide detailed descriptions of membrane anatomy-based radical resection for middle transverse colon cancer. Over the years, our center has applied the concept of membrane anatomy to clinical practice in radical resection of middle transverse colon cancer, resulting in a standardized and easily mastered surgical protocol. This article shares our team’s experience in performing this surgery.